Relationship between Neonatal septicemia and birth weight - Al-Bayaa, Yasmeen J.; Ayoub, Nedhal S.; NajemAlwan, Sevan (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Neonatal Septicemia (NNS) is generalized microbial symptomatic infection during the first 28 days of life.It>s the most serious complication in Neonatal Intensive Care Units (NICU) that demand urgent diagnosis and accurate treatment. Objective: To reveal the relationship of neonatal septicemia with birth weight (one of the neonatal risk factors). Patients and Methods: Blood sample was obtained from 76 neonates aged 1 hour-28 days who were diagnosed clinically (poor feeding, respiratory distress, fever, hypothermia, gastrointestinal and/or central nervous system symptoms)and bacteriologically to have neonatal septicemia. Results:One of the most important neonatal factor predisposing to infection is low birth weight, significant positive culture results were found among the group with birth weight 0.9–2 Kg.Gram negative bacteria constituted 71% of the total isolates. Conclusion: The low birth weight infants were at high risk to neonatal Septicemia.